2016
DOI: 10.5194/cp-12-2271-2016
|View full text |Cite
|
Sign up to set email alerts
|

The simulated climate of the Last Glacial Maximum and insights into the global marine carbon cycle

Abstract: Abstract. The ocean's ability to store large quantities of carbon, combined with the millennial longevity over which this reservoir is overturned, has implicated the ocean as a key driver of glacial-interglacial climates. However, the combination of processes that cause an accumulation of carbon within the ocean during glacial periods is still under debate. Here we present simulations of the Last Glacial Maximum (LGM) using the CSIRO Mk3L-COAL (Carbon-OceanAtmosphere-Land) earth system model to test the contri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 162 publications
(217 reference statements)
8
44
1
1
Order By: Relevance
“…Without the effect of ocean volume reduction, the combination of physical processes and carbonate chemistry can explain up to 57 ppm at the LGM and on average 38 ppm during the entire 400 kyr time interval (see Table 2). This is consistent with the recent results by Buchanan et al (2016) and Kobayashi et al (2015). Note that simulated changes in silicate weathering and its impact on atmospheric CO 2 are small, as has already been shown in Brovkin et al (2012).…”
Section: The Standard Carbon Cycle Model Setupsupporting
confidence: 82%
“…Without the effect of ocean volume reduction, the combination of physical processes and carbonate chemistry can explain up to 57 ppm at the LGM and on average 38 ppm during the entire 400 kyr time interval (see Table 2). This is consistent with the recent results by Buchanan et al (2016) and Kobayashi et al (2015). Note that simulated changes in silicate weathering and its impact on atmospheric CO 2 are small, as has already been shown in Brovkin et al (2012).…”
Section: The Standard Carbon Cycle Model Setupsupporting
confidence: 82%
“…Deep water was evidently less oxygenated than at present (Duplessy, 1982;Kallel et al, 1988;Schmiedl and Leuschner, 2005;Waelbroeck et al, 2006). This was reproduced by models that showed a generally more sluggish bottom water ventilation from the Antarctic (Rickaby and Elderfield, 2005) with reduced oxygen contents due to the increase in sea ice cover (Buchanan et al, 2016;Somes et al, 2017). A better ventilation of the upper water column in the glacial ocean was explained by the better oxygen solubility in the colder water (Somes et al, 2017).…”
Section: Study Areasupporting
confidence: 54%
“…However, the diversity of oxygen proxies makes the glacial oxygen depletion likely very robust: the model is clearly missing something. Buchanan et al (2016) found a similar increase in deep ocean O 2 in a well-equilibrated simulation with the CSIRO coupled model under glacial boundary conditions, suggesting one or more missing elements may be common in the response of existing models to LGM radiative and ice sheet forcing. We propose three non-exclusive hypotheses for what might cause these models to grossly overestimate the glacial deep ocean oxygen content.…”
Section: Glacial Nitrate Deep Ocean O 2 and Carbon Storagementioning
confidence: 62%
“…Deepening of the remineralization profile, as would have resulted from slow ecosystem metabolism under low temperatures (Matsumoto et al 2007), could have contributed to low deep ocean oxygen concentrations, though again it seems unlikely to explain the surface nitrate depletion. Simulations previously made by Buchanan et al (2016) and Galbraith and Jaccard (2015) suggest that the combination of increased export production and deeper remineralization (together with the 200-year age underestimate) could possibly close the gap between the CM2Mc glacial state and the existing LGM oxygen observations. Testing these hypotheses would benefit from improved quantitative estimates of dissolved oxygen and export production, and from future model simulations that include additional tracers (e.g.…”
Section: Glacial Nitrate Deep Ocean O 2 and Carbon Storagementioning
confidence: 81%
See 1 more Smart Citation